Eksplorasi Pola Pembelian Konsumen Di E-Commerce Menggunakan Algoritma FP-Growth - Hamonangan, Ryan; Arie Wijaya, Yudhistira (CV. Multi Kreasi Media, 2023)
This study aims to explore consumer purchasing patterns on e-commerce platforms using the FP-Growth (Frequent Pattern Growth) algorithm. With the rise of e-commerce, it is crucial for platform managers to understand existing purchasing patterns in order to design more effective marketing strategies. The FP-Growth algorithm is chosen due to its efficiency in extracting association patterns, especially in large datasets. The data used in this research was obtained from purchase transactions on an e-commerce platform, including the items purchased by consumers over a specific time period. The results of this study reveal frequent purchasing patterns and product associations that can help platform managers design better product recommendations. The FP-Growth algorithm provides valuable insights to enhance consumer shopping experiences and the effectiveness of marketing strategies on e-commerce platforms.